Monads and tensor products - Radul, T. N. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
M. Zarichnyi defined an operation of tensor product for each functor that can be complemented to a monad. We investigate the existence of tensor product for functors which cannot be complemented to monads.